Functionality and translation fidelity characterization of mRNA vaccines using platform based mass spectrometry detection - Alyssa Q. Stiving; Benjamin W. Roose; Christopher Tubbs; Mark Haverick; Ashley Gruber; Richard R. Rustandi; Jesse Kuiper; Matthew Schombs; Hillary Schuessler; Xuanwen Li (npj Vaccines)
Abstract The success of mRNA-based therapeutics and vaccines is attributed to their rapid development, adaptability, and scalable production. Modified ribonucleotides like N1-methylpseudouridine enhance stability and reduce immunogenicity but were recently found to induce cellular immunity to off-target, +1 ribosomal frameshifted protein. We developed a new platform using cell-free translation (CFT) and liquid chromatography-tandem mass spectrometry (MS) to detect, characterize, and quantify antigen proteins from mRNA constructs. This workflow enabled evaluation of mRNA functionality under thermal stress and assessment of multivalent formulations with high sequence homology. The MS approach was further applied following cell-based translation and demonstrated high sensitivity and specificity, accurately identifying all six translated proteins and their relative abundances from a hexavalent mRNA drug product in a dose-dependent manner. Furthermore, the CFT-MS approach successfully identified +1 ribosomal frameshifting linked to N1-methylpseudouridylation. This methodology provides a valuable analytical tool for assessing mRNA quality and functionality in vaccine development and beyond.